2021
DOI: 10.1002/bem.22374
|View full text |Cite
|
Sign up to set email alerts
|

One‐time Electromagnetic Irradiation Modifies Stress‐sensitive Gene Expressions in Rice Plant

Abstract: Electromagnetic energy is utilized over multiple frequency bands to provide seamless wireless communication services. Plants can well perceive electromagnetic energy present in open environment due to reasonably high permittivity and electrical conductivity of constituent tissues. Moreover, higher surface-to-volume ratio of plant structure facilitates increased interaction with the incident electromagnetic waves. To date, a few well-designed studies have been conducted inside controlled electromagnetic reverbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…This observation is in line with relevant articles published in recent times [9-15, 24, 72, 73]. Hence, global policymakers should promote further research on subsequent biological effects at plant physiological as well as molecular levels and revise existing electromagnetic exposure policies based on the findings [62][63][64][65][66].…”
Section: Discussionsupporting
confidence: 86%
“…This observation is in line with relevant articles published in recent times [9-15, 24, 72, 73]. Hence, global policymakers should promote further research on subsequent biological effects at plant physiological as well as molecular levels and revise existing electromagnetic exposure policies based on the findings [62][63][64][65][66].…”
Section: Discussionsupporting
confidence: 86%
“…A single 2.5-h exposure of 12-d-old seedlings also caused changes in gene expression ( Kundu et al 2021a ). Upregulation of stress-related genes, e.g., calmodulin and phytochrome B, was also observed after a single exposure of 40-d-old rice plants ( Kundu et al 2021b ).…”
Section: Resultsmentioning
confidence: 98%
“…Because they often have a higher surface-to-volume ratio than most other living things, plants are a great choice for studying the biological reactions that electromagnetic radiation causes and the impacts that follow [18,19,20,21]. Studies on the physiological and chemical reactions that plants experience when exposed to electromagnetic radiation on a regular or one-time basis have been conducted throughout the last two decades [22][23]. Because it instantly changes plant gene expressions that are susceptible to stress, controlled www.jchr.org JCHR (2024) 14(1), 2369-2377 | ISSN:2251-6727 electromagnetic exposure is thought to be analogous to wounding [18,20, 22&23].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, none of the publications discussed how electromagnetic radiation had lingering physiological impacts in plants. i.e., all published research on the subject has shown instantaneous reactions in plants to either one-time or repeated electromagnetic radiation [18][19][20][21][22][23][24][25][26][27][28]. Furthermore, since target plant specimens were not exposed to regulated electromagnetic fields, a number of earlier investigations were unable to provide definitive findings.…”
Section: Introductionmentioning
confidence: 99%